EDUKASI PEMILIH MUDA DALAM PILKADA DI OGAN ILIR SUMATERA SELATAN - Alamsyah Alamsyah; Zulfikri Suleman; Eva Lydia; Dadang Hikmah Purnama; Sylvie Agustina (LP2M Universitas Ibrahimy, 2023)
At present, especially in Ogan Ilir District, the COVID-19 pandemic conditions had triggered a food war between candidates in the 2020 Ogan Ilir Regional Election (pilkada). Although social media, particularly Facebook, facilitates voter participation in various political issues in the regional elections, voters had the potential to became political victims because they consumed fake news, slander, and hate speech. One of the layers of the population that was vulnerable to becoming victims was youth voters (17-23 years old). As youth voters will continue the political leadership relay in Ogan Ilir District, there should be a systematic effort to increase their thinking and political awareness. Even though every day they was presented with patronage practices and emotional political relations, youth voters should be given the opportunity to understand and elaborate election contestation from a different perspective. Money politics may not be prevented, but the young generation must still be introduced to the concept of the ideal pilkada. This service activity was designed to increase the political knowledge of the officials/members of the Karang Taruna in Ogan Ilir District with the tutorial lecture and group discussion methods. The contribution of this service activity to the increase in knowledge and political insight of the participants was proven statistically, t(52) = 11.25, p <0.001. This article recommends that similar activities be carried out in a sustainable manner by various parties with an interest in the process of empowering the younger generation.